Genetic and Structural Network Contributions to The Regional Vulnerability of Tauopathy. (20th December 2022) - Wen, Qiuting; Yu, Meichen; Shahid, Syed Salman; Zhao, Yi; Risacher, Shannon L.; Saykin, Andrew J.; Wu, Yu‐Chien
Abstract: Background: Tau propagates in a highly stereotyped pattern in both normally aged and cognitively impaired individuals, with the medial temporal lobe (MTL) being first affected. Although substantial progress has been made in revealing its spreading pattern with the aid of network analysis, it remains unclear why tau first seeds in this specific region. We hypothesize that regional white‐matter connections exacerbate MTL's vulnerability to tauopathy. Further, we speculate that tau candidate genes have higher expression levels in MTL. This study tested the two hypotheses in cognitively normal older brains using two independent imaging datasets, i.e., ADNI and Indiana ADRC (IADRC), along with gene expression data derived from the Allen Human Brain Atlas (AHBA). Method: We identified 159 cognitively normal participants (72±7 y/o) in ADNI and 57 (70±7 y/o) in IADRC that have both diffusion MRI and tau‐PET (AV1451) data. We estimated network metrics and tau SUVR in 68 cortical regions of interest (ROIs) for each participant. All participants' data were then averaged (after controlling for age and sex) to produce ROI‐wise measurements. Gene expression data were extracted from the same 68 ROIs. We preselected eight tau risk genes, including MAPT, LRP1, PTK2B, MADD, CASS4, BIN1, EPHA1, and APOE . Spearman correlation was applied to examine their spatial correlations. Result: ADNI and IADRC reveal a similar spatial pattern for structural connectivity and tau deposition, with MTL demonstrating lower connectivity and higher gene expression levels (Figure 1A‐B). This trend is also evident when summarized in Braak stages (Figure 1C‐D), with Braak I ROI (entorhinal) showing the most elevated tau deposition, lowest structural connectivity, and highest gene expression level. Figure 2 summarizes the Spearman's Rho across the 68 ROIs. Consistently, higher tau deposition is associated with lower connectivity and higher the expression levels of BIN1 and APOE . Conclusion: The two independent datasets produced consistent results, supporting our hypotheses that both weaker structural connectivity and higher tau candidate gene expression contribute to the regional vulnerability in the MTL. These preliminary results encourage future studies to systemically examine the interaction between tau, gene expression, and axonal changes in healthy aging and across the AD spectrum.